Pengaruh Penerapan Alat Peraga Puzzle dengan Menggunakan Metode Demonstrasi Terhadap Motivasi Belajar Siswa Pada Pembelajaran Matematika di SD/MI - Ahmad Arifuddin; Syibli Maufur; Farida Farida (Universitas Pendidikan Ganesha, 2018)
AbstractThis study aims to determine how much influence the application of puzzle props by using demonstration methods to student’s learning motivation on learning mathematics in SD / MI. This research is a quantitative research, using One Shot Case Study design. Data collection techniques used were questionnaires and observations. Subjects in this study were all students of grade IV-1 MI An-Nur Cirebon City which amounted to 38 students. The technique of data analysis used in this research is questionnaires test, determination test and Coefisient Regression Test. Based on regression test results, it is found that the significance value of 0.000. So that the significance value is smaller than 0.05 and t arithmetic of 6,608 is greater than t table of 2.03011, then Ho is rejected. This means that the application of puzzle props by using demonstration method on learning mathematics have a significant influence to student's learning motivation in class IV MI An-Nur Cirebon City.